Fiber Optic Network Innovations to Bypass the Red Sea Route - E., Raj; M., Dhanalakshmi K. (Journal of Electronics and Informatics, 2025)
This ambitious project seeks to establish a robust, high-speed fiber optic network that will connect Europe with South Asia through a terrestrial route spanning Saudi Arabia, Iraq, Turkey, Bulgaria, Hungary, and Austria. The project presents a strategic alternative to traditional maritime internet cables, which often traverse underwater routes from Europe to South Asia. By relying on a land-based network, this initiative aims to mitigate some of the risks associated with undersea cables, such as disruptions caused by natural disasters, shipping accidents, or geopolitical tensions in maritime zones. One of the key components of this project is infrastructure development. This involves laying extensive fiber optic cables, building data centers, and ensuring that the network is both secure and scalable. Unlike the challenges faced by undersea networks, land-based infrastructure allows for easier maintenance, potential expansions, and faster upgrades to meet future demands for higher data speeds and increased bandwidth. Technology integration plays a crucial role as well. Advanced networking technologies like 5G, edge computing, and cloud services can be integrated into this fiber optic network, enabling the efficient handling of vast amounts of data and enhancing overall performance. The deployment of state-of-the-art technologies will also help in reducing latency, improving user experience, and fostering innovation in the region.